Proceedings of the First Workshop on Recent Advances on Intrusion-Tolerant Systems - Correia, Miguel (2009)
The First Workshop on Recent Advances on Intrusion-Tolerant Systems aimed to bring together researchers in the related areas of Intrusion Tolerance, Distributed Trust, Survivability, Byzantine Fault Tolerance, and Resilience. The workshop was specially interested in ``intrusion-tolerant systems': how to build them? How to evaluate and test their dependability and security? What systems need to be intrusion-tolerant? The proceedings contain 7 papers, and the abstract of the keynote speech by Professor William H. Sanders, from University of Illinois at Urbana-Champaign